Sugar Protectants Improve the Thermotolerance and Biocontrol Efficacy of the Biocontrol Yeast, Candida oleophila - Zheng, Fangliang; Zhang, Weiwei; Sui, Yuan; Ding, Ruihan; Yi, Wenfu; Hu, Yuanyuan; Liu, Hongsheng; Zhu, Chunyu (Frontiers in Microbiology, 2019)
A variety of sugar compounds have been used as additives to protect various biocontrol yeasts from adverse environmental stresses. However, studies on maltose and lactose as sugar protectants are limited, and their protective effect is not clear. In the present study, exposure of the biocontrol yeast Candida oleophila cells to 45 oC for 10 min, while immersed in either 5% or 10% (w/v) maltose or lactose, provided a significant protective effect. The addition of maltose and lactose significantly enhanced enzyme activity and gene expression of catalase, thioredoxin reductase, and glutathione reductase, relative to cells that had been immersed in sterile distilled water (controls) exposed to 45 oC. In addition, C. oleophila cells suspended in maltose and lactose solutions also exhibited higher viability and ATP levels, relative to control cells. Notably, the biocontrol efficacy of C. oleophila against postharvest diseases of apple fruit was maintained after the yeast was exposed to the high temperature treatment while immersed in maltose and lactose solutions. These results demonstrate the potential of maltose and lactose as sugar protectants for biocontrol agent against heat stress.